Monuments, Movements, and the Photography of Jeff Thomas. Discussion between Mikinaak Migwans (Curator of Indigenous Art, Art Museaum) and Maria Hupfield, with Syrus Marcus Ware - Thomas, Jeff
Interview vidéo et écrite.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé